Synthesis of highly stable silver nanoparticles as computed tomography contrast agents - Nguyen Thi Ngoc, Linh; Le The Tam (Vietnam Journal of Science and Technology, 2023)
In this work, highly stable Ag nanoparticles solution was synthesized using TBAB to reduce Ag+ in the presence of OLA in organic solvents at room temperature, and poly(acrylic acid) (PAA) as a phase transfer ligand in organic solvents. The effects of different solvents on the morphology and properties of the Ag nanomaterials were investigated in detail. The products were characterized by using transmission electron microscopy (TEM), X-ray diffraction (XRD), and absorption spectroscopy. Structural analysis demonstrated that the Ag nanomaterials showed good crystallinity. We have successfully synthesized Ag nanoparticles (Ag NPs) with small particle size (6.1 - 7.3 nm), high uniformity in organic solvents at room temperature. The Ag NPs obtained after phase transformation with PAA are well dispersed, endurance and stability in aqueous solvents. The obtained in-vitro CT imaging results have good X-ray absorption value. These findings suggest the potential application of PAA-coated Ag nanoparticles in the biomedical field, especially in imaging diagnostics using CT computed tomography.